Improvement of the Effects Dispersion Model for Jets in Cross Flow - Andreas Mack (Chemical Engineering Transactions)
The present paper describes the modelling of vertical jets in crossflow in the consequence modelling software EFFECTS v12.4, based on an integral modelling approach, including validation in a wide range of density variation of the released substance.